Generation and Characterization of the Anp32e-Deficient Mouse - Reilly, Patrick T. (Public Library of Science, 2010)
BACKGROUND: Accumulated literature suggests that the acidic nuclear phosphoprotein 32 kilodalton (Anp32) proteins control multiple cellular activities through different molecular mechanisms. Like other Anp32 family members, Anp32e (a.k.a. Cpd1, PhapIII) has been conserved throughout vertebrate evolution, suggesting that it has an important function in organismal survival. PRINCIPAL FINDINGS: Here, we demonstrate that the Anp32e gene can be deleted in mice without any apparent effect on their wellbeing. No defects in thymocyte apoptosis in response to various stresses, fibroblast growth, gross behaviour, physical ability, or pathogenesis were defined. Furthermore, combined deletion of Anp32a and Anp32e also resulted in a viable and apparently healthy mouse. SIGNIFICANCE: These results provide evidence that significant functional redundancy exists among Anp32 family members.